Focus group reflections on the current and future state of cognitive assessment tools in geriatric health care - Whitehead JC (Dove Medical Press, 2015)
Jocelyne C Whitehead,1 Sara A Gambino,1 Jeffrey D Richter,2 Jennifer D Ryan1,3,41Rotman Research Institute, Baycrest, 2Independent Human Factors Consultant, Toronto, ON, Canada; 3Department of Psychology, 4Department of Psychiatry, University of Toronto, Toronto, ON, CanadaObjective: This study provides insight into the thoughts and opinions of geriatric health-care professionals toward cognitive assessments and the use of emerging technologies, such as eye-tracking, to supplement current tools.Methods: Two focus group sessions were conducted with nurses and physicians who routinely administer neurocognitive assessments to geriatric populations. Video recordings of the focus group sessions were transcribed and a thematic analysis was performed.Results: Participants reported the need for assessment and diagnostic tools that are accessible and efficient, and that are capable of accommodating the rapid growth in the aging population. The prevalence of more complex ailments experienced by older adults has had repercussions in the quality of care that the clients receive, and has contributed to lengthy wait times and resource shortages. Health-care professionals stated that they are hampered by the disjointed structure of the health-care system and that they would benefit from a more efficient allocation of responsibilities made possible through tools that did not require extensive training or certification. Eyetracking-based cognitive assessments were thought to strongly complement this system, yet it was thought that difficulty would be faced in gaining the support and increased uptake by health-care professionals due to the nonintuitive relationship between eyetracking and cognition.Conclusion: The findings suggest that health-care professionals are receptive to the use of eyetracking technology to assess for cognitive health as it would conserve resources by allowing frontline staff to administer assessments with minimal training.Keywords: neurocognitive assessment, eyetracking, focus groups, geriatric health care